2022
DOI: 10.1111/scd.12808
|View full text |Cite
|
Sign up to set email alerts
|

Impression technique modification and oral contracture release surgery for orthodontic treatment in a patient with severe microstomia due to recessive dystrophic epidermolysis bullosa

Abstract: IntroductionEpidermolysis bullosa (EB) is a group of genetic disorders characterized by fragility of the skin and mucosal membranes. Dystrophic EB (DEB) is caused by mutations in the gene coding for type VII collagen. Among the most frequent oral manifestations in Recessive DEB (RDEB) are oral ulcers and blisters, absence of tongue papillae and palatal rugae, ankyloglossia, oral vestibule obliteration, and microstomia. The following report describes a modified impression technique used in a patient with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Even after this, the authors had to develop a flexible custom‐made tray because the mandibular width at the lower molar area was larger than the width of the mouth during maximal mouth opening. They used a thermoplastic sheet to create a flexible tray and obtained the impressions for the aligner's design for treating the patient 17 . Similarly in our case, the multidisciplinary team approach was crucial for achieving success, as the periodontal surgery to deepen the oral vestibule enabled the placement of the miniscrews, and the oral rehabilitation team provided an aesthetic and stable anterior teeth rehabilitation.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Even after this, the authors had to develop a flexible custom‐made tray because the mandibular width at the lower molar area was larger than the width of the mouth during maximal mouth opening. They used a thermoplastic sheet to create a flexible tray and obtained the impressions for the aligner's design for treating the patient 17 . Similarly in our case, the multidisciplinary team approach was crucial for achieving success, as the periodontal surgery to deepen the oral vestibule enabled the placement of the miniscrews, and the oral rehabilitation team provided an aesthetic and stable anterior teeth rehabilitation.…”
Section: Discussionmentioning
confidence: 73%
“…First, the lack of attached gingiva did not allow a correct placement of the miniscrews. With a 2 mm depth, it was necessary to increase the vestibule with a periodontal surgery, similar to the surgery described by Véliz et al 17 Once the miniscrews were placed, the vestibule obliteration and the lack of mobility of the upper lip occasionally produced traumatic wounds in the mucosa due to the head of the miniscrew, which measured 3 mm approximately. This was managed with the use of orthodontic wax, commonly used in orthodontics and also described by Pacheco and de Souza.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the occurrence of microstomia due to various causes such as trauma, cancer ablation surgery, or burns, patients may be treated by either reusing their existing dentures or creating new ones using different types of dental impression trays, which include both conventional and digital methods applied serially [ 1 , 2 , 20 , 53 ]. There are studies that categorize oral appliances based on their shape, direction, and position.…”
Section: Treatment Of Microstomiamentioning
confidence: 99%
“…It has been reported that excellent outcomes can be achieved by employing the various surgical treatment methods introduced earlier and by immediately placing dentures or prosthetics [ 53 , 90 ].…”
Section: Treatment Of Microstomiamentioning
confidence: 99%